The Relationship Between Teachers' Communication Skills and Organizational Climate - Ataç, İsmail; Bilgivar, Orkun Osman (Fırat University, 2023)
The aim of this study is to reveal whether there is a relationship between teachers' communication skills and organizational climate. Correlational survey research method, one of the quantitative research methods, was used in the research. The study group consists of 351 teachers working in Kartal district of Istanbul in the 2021-2022 academic year. The data obtained as a result of the research were analyzed using correlation and regression analysis. The result show that, teachers state that their principals exhibit the most supportive principal behavior. When teachers use ego-enhancing language and show empathy, the supportive behaviors of the administrators increase, as well as the restrictive and commanding behaviors of the administrators decrease. In addition, teachers perceive that their colleagues show the most cooperative behavior. Moreover, collaborative teacher behaviors increase if teachers emphasize their competencies while communicating with their colleagues and make them feel that they are listening to them effectively. It was concluded that when teachers use ego-enhancing language, they increase the productivity of their colleagues. Based on the findings, in the last part of the research, suggestions were made to school administrators and teachers about which communication skills they should use in order to create a positive organizational climate in the school.

Bu çalışmanın amacı öğretmenlerin iletişim becerileri ile örgütsel iklim arasında ilişki olup olmadığının ortaya çıkarılmasıdır. Araştırmada nicel araştırma yöntemi ve ilişkisel tarama deseni kullanılmıştır. Araştırmanın çalışma grubu 2021-2022 Eğitim Öğretim yılında İstanbul ili Kartal ilçesinde görev yapmakta olan 351 öğretmenden oluşmaktadır. Elde edilen veriler betimsel istatistik (ortalama, standart sapma), korelasyon ve regresyon analizleri kullanılarak çözümlenmiştir. Bulgular incelediğinde, öğretmenler yöneticilerinin en çok destekleyici müdür davranışı sergilediklerini ifade etmektedirler. Öğretmenler egoyu geliştirici dil kullandıklarında ve empati yaptıklarında yöneticilerin destekleyici davranışları artmakta bunun yanı sıra yöneticilerin kısıtlayıcı ve emredici davranışları azalmaktadır. Yine öğretmenler meslektaşlarının en çok işbirlikçi öğretmen davranışı gösterdiklerini düşünmektedir. Ayrıca öğretmenler meslektaşları ile iletişim esnasında onların eksik yönlerini dile getirirken yeterliliklerini öne çıkarır ve etkin bir şekilde onları dinlediklerini hissettirirlerse işbirlikçi öğretmen davranışları artmaktadır. Öğretmenler egoyu geliştirici dil kullandıklarında meslektaşlarının verimini arttırdıkları sonucuna ulaşılmıştır. Elde edilen bulgulardan hareketle araştırmanın son bölümünde okul yöneticilerine ve öğretmenlere okul içinde olumlu bir örgütsel iklim oluşması için hangi iletişim becerilerini kullanmaları konusunda önerilerde bulunulmuştur.
ÖĞRETMENLERİN İLETİŞİM BECERİLERİ İLE ÖRGÜTSEL İKLİM ARASINDAKİ İLİŞKİ
Keywords: Applied Linguistics and Educational Linguistics; Uygulamalı Dilbilim ve Eğitim Dilbilimi